Sound absorption coefficient and water content responses in acoustic analysis based on renewable polyurethane foam composites - Abdul Wahab, Hanani; M. Rus, Anika Zafiah; Abdullah, M. F. L.; Abdullah, Nur Munirah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In physiological health, negative effects are felt when unwanted noise is present. Given the negative effects of the unwanted noise, it become important to examine how environmentally-friendly and efficient sound absorbing materials could be developed. Some of the materials associated with acoustic absorption properties entail polymer foams. Particularly, the foams aid in controlling noise. The central purpose of this study was to examine renewable polymer (PU) foam composites’ aspects of moisture content and acoustical properties. Four major parameters that were evaluated included the thickness of the sample, the type of filler, the ratio of the fillers, and the nature of the monomer. A design of experiment (DoE) technique was employed. To prepare the PUs foams, 28 mm and 100 mm were selected as diameters for the cylindrical shapes on focus. Plotting the main effects was achieved through ANOVA, upon which variations in the role and performance of the selected input factors were discerned. From the findings, it was established that when bio-epoxy (B) was used in conjunction with renewable PU foams, the moisture content was greater than the case involving petroleum based PU foam synthesis. Hence, renewable PU foam composite is seen to be realized at 0.9, especially if the filler ratios and size are increased; with the experimental conditions set at 3 kHz. Overall, the study established that the renewable Pus’ state of sound absorption exhibits good agreement with the case of synthetic PU foam.